Lack of association between provocative test-based intraocular pressure parameters and functional loss in treated glaucoma patients - Scoralick,Ana Luiza Bassoli (2019)
ABSTRACT Purpose: To correlate provocative test-based intraocular pressure (IOP) variation parameters (fluctuation and peak) with functional status, and to compare these IOP parameters between treated eyes with asymmetric primary open-angle glaucoma (POAG). Methods: A prospective observational study including consecutively treated patients with primary open-angle glaucoma was performed. Subjects with ocular diseases other than glaucoma or previous incisional glaucoma surgery were excluded. The primary inclusion criteria were 33 visual field tests and 32 years of follow-up, without any changes on current medical regimen. Long-term intraocular pressure parameters were acquired via isolated intraocular pressure measurements from the patients' last 5 office visits. To evaluate provocative test-based intraocular pressure parameters, all patients were submitted to a water drinking test. Initially, the partial correlation coefficients between each intraocular pressure variation parameter and visual field mean deviation were calculated, adjusting for the baseline intraocular pressure and number of antiglaucoma medications. In addition, each intraocular pressure parameter was compared between eyes with better visual field mean deviation and fellow eyes with worse visual field mean deviation in patients with asymmetric visual field loss (defined as an inter-eye visual field mean deviation difference of at least 3 dB). Results: A total of 87 eyes (87 patients; mean age, 61.9 ± 12.5 years; 59.8% women) with primary open-angle glaucoma were included. The patients underwent a median of 5 visual field tests, with a mean follow-up of 4.3 ± 1.4 years. Neither long-term nor water-drinking test intraocular pressure variation parameters were significantly associated with visual field mean deviation values (p30.117). In the subgroup with asymmetric visual field loss (64 eyes of 32 patients; mean age, 65.0 ± 11.4 years), neither long-term water-drinking test intraocular pressure variation parameters differed significantly between eyes with better and worse visual field mean deviation (p30.400). Conclusion: Our results indicate that neither long-term intraocular pressure variation parameters nor stress test-derived intraocular pressure metrics, as assessed by the water-drinking test, appear to correlate with the visual field status or differ significantly between eyes with asymmetric visual field damage, suggesting that other factors may explain such functional asymmetry, and that the water-drinking test does not add significant information to these cases.